The analysis of companies’ business as a aystem of collection, research and evaluation of information - Mackevičius, Jonas (Information & Media, 2008)
A new definition of the analysis of companies’ business was formulated: the analysis of companies’ business is a collection, investigation and evaluation of economic information in order to achieve the goals set by the management of the company. The analysis of companies’ business collects, investigates and evaluates information about all company’s business operations, including its main activities (production, commercial), financing and investment activities. Thus, a new formula was suggested: the analysis of companies’ business = the analysis of main activities + the analysis of financial activities + the analysis of investment activities.Based on the research data of foreign and Lithuanian, the content of the analysis of main, financial and investment activities was presented. This content includes the most important topics the detailed analysis of which would help to evaluate companies’ financial condition, business results, cash flows and to forecast their business perspectives.